Cytoplastic Glyceraldehyde-3-Phosphate Dehydrogenases Interact with ATG3 to Negatively Regulate Autophagy and Immunity in Nicotiana benthamiana. Issue 4 (31st March 2015) - Han, Shaojie; Wang, Yan; Zheng, Xiyin; Jia, Qi; Zhao, Jinping; Bai, Fan; Hong, Yiguo; Liu, Yule
Abstract : ATG3 interacts with GAPCs, which negatively regulate autophagy and play an essential role in effector-triggered immunity and basal defense. The interaction between GAPCs and ATG3 is regulated by ROS. Abstract: Autophagy as a conserved catabolic pathway can respond to reactive oxygen species (ROS ) and plays an important role in degrading oxidized proteins in plants under various stress conditions. However, how ROS regulates autophagy in response to oxidative stresses is largely unknown. Here, we show that autophagy-related protein 3 (ATG3) interacts with the cytosolic glyceraldehyde-3-phosphate dehydrogenases (GAPCs ) to regulate autophagy in Nicotiana benthamiana plants. We found that oxidative stress inhibits the interaction of ATG3 with GAPCs . Silencing of GAPCs significantly activates ATG3 -dependent autophagy, while overexpression of GAPCs suppresses autophagy in N. benthamiana plants. Moreover, silencing of GAPCs enhances N gene-mediated cell death and plant resistance against both incompatible pathogens Tobacco mosaic virus and Pseudomonas syringae pv tomato DC3000, as well as compatible pathogen P. syringae pv tabaci . These results indicate that GAPCs have multiple functions in the regulation of autophagy, hypersensitive response, and plant innate immunity.